HUMAN RESOURCE MANAGEMENT, MANUFACTURING STRATEGY, AND FIRM PERFORMANCE. - YOUNDT, M. A.; SNELL, S. A.; DEAN, JR., J. W.; LEPAK, D. P. (Academy of Management Journal, 1996)
This study examines two alternative views—universal and contingency—of the human resources (HR)-performance relationship in manufacturing settings. Results from a survey of 97 plants primarily support a contingency approach to human resource management (HRM). An HR system focused on human capital enhancement was directly related to multiple dimensions of operational performance (i.e., employee productivity, machine efficiency, and customer alignment), but subsequent analysis revealed that this main effect was predominately the result of linking human-capital-enhancing HR systems with a quality manufacturing strategy. Other manufacturing strategies also moderated the HR-performance relationship.